Catch, Effort and Distribution of Small Pelagic Fisheries in the Java Sea - Ilham; Yonvitner; Mennofatria Boer; Rahmat Kurnia; Zairion (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2025)
Fisheries management area (FMA) 712 or the Java Sea is one of Indonesia's most extensively exploited waters and is renowned forits productivity as a fishing ground. The dynamics of fish resource utilization in these waters are indicative of the high complexityof the extant fisheries system, with small pelagic fish resources having been subject to exploitation through various changes in geartechnology thus increasingly competitive fishing grounds. Therefore, there is a need data on current distribution and catch trend ofsmall pelagic fisheries in the Java Sea through the use of fishery dependent data as an integral part of sustainable fisheriesmanagement. The present study utilizes fishing logbook data to analyze the status of small pelagic fish resource utilization in theJava Sea. The study utilized fishing logbook data downloaded from the database application of the Fishing Logbook InformationSystem of the Indonesian Ministry of Marine Affairs and Fisheries, covering the period from 2018 to 2022. The subsequentprocessing of catch data was conducted using Microsoft Excel software, whereas the distribution of fishing areas was analyzed usingQGIS tools. The analysis revealed a tendency for a decline in the catch of small pelagic fisheries for the Indian Mackerel(Rastrelliger kanagurta), Short Mackerel (Rastrelliger brachysoma), Fringescale Sardinella (Sardinella fimbriata) and ShortfinScad (Decapterus macrosoma). Only Yellowstripe Scad (Selaroides leptolepis) showed an increased catch trend in that period. Itwas further observed that the fishing grounds of all fish species remained consistent on an annual basis. The Shortfin Scad fishinggrounds were found to be uniformly dispersed within FMA 712, exhibiting a tendency to congregate along the Java Sea border withBorneo waters. Short Mackerel have been observed to be frequent in fishing grounds of the eastern to western Java Sea. In contrast,Indian Mackerel have been noted to be more prevalent in the waters of South Borneo and the western Java Sea. The distribution ofYellowstripe Scad fishing grounds appears to be uniform within FMA 712. Fringescale Sardinella fishing grounds have beenidentified as being predominantly concentrated in the western Java Sea and in Borneo waters.